Study on the control effect of two different forms of side suction hoods on pollutants. Issue 2 (September 2019) - Xiong, Han; Peng, Xiaoyong; Li, Yu; Chen, LiYuan
Abstract: A suitable exhaust hood form has a great influence on the control effect of pollutants. This paper uses CFD technology to numerically simulate the airflow distribution characteristics and pollutant concentration distribution characteristics of the side hood before and after improvement. The results show that: (1) The airflow of the improved side suction hood is introduced from the front of hood to make the fresh air pass through the breathing area first and then takes away the hazardous substances, which is beneficial to the breathing health of workers. (2) When the exhaust velocity (V) is more than 3.5m/s, with the increase of the exhaust velocity, the concentration hazardous substances at each control point of the two forms of exhaust hood tends to be stable gradually. (3) When the exhaust velocity is less than 3.5m/s, the control effect of side suction hood with baffle is better than that without baffle, and the percentage of hazardous substances concentration at the same control point can be reduced by 12%-29%, or even higher.